Ideologia e religião: uma leitura marxista de Contra os cristãos, de Porfírio - Sérgio Luiz Gusmão Gimenes Romero (2023)
This work comprises two fundamental aspects: a theoretical reflection on the study of the religious phenomenon based on Marxist social theory and an analysis, based on this framework, of elements related to the treatise Against the Christians, by Porphyry of Tire (ca. 234-305), Neoplatonic philosopher of Late Antiquity. The proposed objectives focus on elucidating, based on theoretical-analytical discussion, how and why specifically religious ideological forms become material forces of transformation or conservation of the social world. Thus, we also seek to outline a general hypothesis for the establishment of the ideological hegemony of Christianity, as a historical crystallization of the religion category itself, in the face of other forms of religiosity typical of Hellenism, due to its functional superiority as a means of social regulation. Of the genesis of this fundamental process for global history, Porphyry and his work are undoubtedly privileged witnesses. To develop this theoretical framework, we draw mainly on the contributions of Karl Marx (1818-1883) and Friedrich Engels (1820-1895) to the understanding and study of religious issues, as well as the late work of György Lukács (1885 -1971) and the recovery of the Marxian social theory carried out by this author. Porphyry’s anti-Christian polemic is thought based on the Marxian theoretical statute, which bases a historical-immanent ontology re-elaborated by Lukács, as well as from his relationships with other authors and with the material and ideological conjunctions characteristics of the social processuality of Late Antiquity under the Roman Empire.